Making Brazil work? Brazilian coalitional presidentialism at 30 and its post-Lava Jato prospects - Katz, Andrea Scoseria (Revista de Investigações Constitucionais, 2018)
The article analyzes the question of coalition presidentialism in the countries of Latin America in general and in Brazil in particular. It offers the reader a close look at coalition presidentialism in all Brazilian governments since the democratization of the country to the present day, presenting the complex relations between Legislative Branch and the Executive Branch in these different moments of Brazilian political reality. The main focus of the article is to relate the impacts of “Lava Jato” operation to this process, seeking to indicate possible consequences of this operation, which caused great repercussion on Brazilian politics, to this scenario of relationship between the Executive and Legislative branches.